Строки захисту права: матеріально-правовий і процесуально-правовий аспекти - Гуйван, Петро Дмитрович; Гуйван, П. Д.; Huivan, Petro D. (Одеса, 2018)
У цій роботі здійснено доктринальне дослідження проблематики взаємодії матеріально-правових та процесуально-правових механізмів регулювання темпоральних проявів реалізації права особи на позов. Визначено особливості здійснення повноважень, закладених у охоронних правовідносинах, у процесуальній формі, яка є засобом їхньої реалізації. Встановлено, що у цьому полягає нерозривний зв’язок матеріального права з процесуальним: матеріальні охоронні відносини виникають і реалізуються паралельно з розвитком процесуальних. Зазначена специфіка їх розвитку та взаємного впливу.

In this work, a doctrinal study of the problems of the interaction of substantive and procedural legal mechanisms for regulating temporal manifestations of the realization of a person’s right to claim is carried out. The features of the implementation of the powers enshrined in the protective legal relationship in the procedural form, which is a means of their implementation. The study is very relevant, since there is no unity in national legislation and scientific doctrine as to what legislation should mediate the mechanism for applying for judicial protection, including in the temporal plane. As a result, we have numerous cases when, in the regulation of protective relations, the law unjustifiably qualifies the periods of limitation as a matter of fact as periods of time for going to court, which should qualify as a lack of legislative regulation. Indeed, in essence, the indicated periods of time, which the law qualifies as terms for going to court, are periods when the victim has a substantive right to bring a claim, that is, a legal action. The substantive relationship to the protection of the right is implemented in procedural form by appeal to the jurisdictional authority. The right to appeal to the court for protection is understood as the right to file a lawsuit in a procedural sense, that is, the right of the person concerned to institute legal proceedings for the consideration and resolution of a particular dispute. The right to appeal to the court is separated from the subjective substantive law: the interested person can apply to the court for protection regardless of whether it is in substantive relations with the defendant, whether his right is violated, the substantive law needs to be protected. The presence or absence of substantive law of the person, the fact of his violation by the defendant is established already when the dispute is considered on its merits. The paper proves the thesis that the realization of a person’s procedural right to go to court directly determines the realization of the right guaranteed by law to the judicial protection of the material right or interest violated. The public legal purpose of justice is, in particular, the establishment of a real legal status of participants in a controversial relationship. Therefore, even with the refusal in the lawsuit to the parties to the dispute, and sometimes to third parties, it is important to achieve certainty in this matter. Therefore, the answer to the following questions should be clearly followed from the court decision: 1) did the plaintiff at the time of the violation belong to the regulatory subjective substantive law for which he applied? 2) Has this right been violated in the manner indicated by the applicant? 3) Is the defendant an offender? 4) Is the protection of the material rights violated by law? This means that the jurisdictional authority must in all circumstances clarify all the circumstances relating to the questions raised. The exercise of the powers enshrined in the protective legal relationship takes place in a procedural form, which is a means of exercising them. This, in fact, is the inextricable link between substantive law and procedural law: material protective relations arise and are realized in parallel with the development of procedural law.
Гуйван П. Д. Строки захисту права: матеріально-правовий і процесуально-правовий аспекти / П. Д. Гуйван // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Одеса, 2018. – Вип. 30. – С. 16-21.
Keywords: матеріальне право на позов; строк звернення до суду; substantive right to claim; term of appeal to court; Research Subject Categories::LAW/JURISPRUDENCE